The role of the dietetary nutrition in the stomach cancer - Stojcev, Zoran; Matysiak, Konrad; Duszewski, Michal; Banasiewicz, Tomasz (Contemporary Oncology/Współczesna Onkologia, 2013)
Stomach cancer mortality still represents a significant proportion of all cancer deaths. The majority of patients with advanced cancer experience cancer anorexia-cachexia syndrome with weight loss, reduced appetite, fatigue, and weakness. Neoplastic cachexia is a very common clinical manifestation of upper gastrointestinal (GI) tract cancer and is generally assumed to be secondary to the mechanical effects of the tumor on the upper digestive tract. The main reasons are obstruction to swallowing, early satiety, nausea and vomiting. Another reason for weight loss is the co- existence of systemic inflammation. Nutritional treatment in the group of patients with gastric cancer is still used too rarely and the knowledge about it is still very limited. Nutritional support should be given for patients both in the pre- and postoperative period. Nutrition should also be used in palliative treatment in patients with unresectable stomach cancer. The main principles of nutritional support and its influence are presented in this publication.